1986
DOI: 10.1177/002246698602000403
|View full text |Cite
|
Sign up to set email alerts
|

Practical Significance in Special Education Research

Abstract: Whereas statistical significance indicates whether a difference is a difference, additional information signifying whether the difference is large enough to make the results worth acting upon is included in practical significance. Statistical measures of practical significance report the extent to which variation in the dependent variable can be explained by the independent variable. Measures of practical significance are seldom reported in The Journal of Special Education, although sometimes issues of practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is not uncommon to find examples of authors stating that a finding is "highly significant" or reporting p values to four or five decimal places, as if something of critical importance were contained in the several zeros preceding the final digit (Feinstein, 1985;Maitland, 1982). Hanson, Abramson, and McNamara (1987) recently demonstrated the fallacy of this assumption in the special education literature. They examined the relationship between magnitude of association measures and probability levels and found that the range of explained variance (10% to 59%) was the same for statistical tests reported significant at the p<.01 and p<.001 levels.…”
mentioning
confidence: 99%
“…It is not uncommon to find examples of authors stating that a finding is "highly significant" or reporting p values to four or five decimal places, as if something of critical importance were contained in the several zeros preceding the final digit (Feinstein, 1985;Maitland, 1982). Hanson, Abramson, and McNamara (1987) recently demonstrated the fallacy of this assumption in the special education literature. They examined the relationship between magnitude of association measures and probability levels and found that the range of explained variance (10% to 59%) was the same for statistical tests reported significant at the p<.01 and p<.001 levels.…”
mentioning
confidence: 99%